Thomas' Calculus 13th Edition

Published by Pearson
ISBN 10: 0-32187-896-5
ISBN 13: 978-0-32187-896-0

Chapter 3: Derivatives - Section 3.2 - The Derivative as a Function - Exercises 3.2 - Page 115: 8


$3s^{2} - 4s$

Work Step by Step

Use derivative formula; $f(x)= x^n \implies f'(x)= n x^{n-1}$ Consider $r(s) = s^{3} -2s^{2} +3$ Take first derivative , we have $r'(s) = 3s^{(3-1)} - 2(2)s^{(2-1)} +0= 3s^{2} - 4s$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.